Comparative analysis of simulated kinetic schemes when calculating the nitrogen oxide formation in solid fuel flaring; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Zueva E. Elena; Vizgavlyust N. V. Nataliya Viktorovna; Vorobyova L. V. Lyudmila Vladimirovna; Starchenko A. V. Aleksandr Vasiljevich (2017, 2017)
Title screen